Magnetic Nanotubes Obtained from Atomic Layer Deposition Coated Electrospun Nanofibers - Escrig-Murua, J; Galotto-Lopez, M; Palma-Solorza, J; Pereira-Abarca, A; Lopez de Dicastillo-Bergamo, A; Patiño-Vidal, C (AVS Science and Technology Society, 2018)
High-aspect ratio Al2O3/Ni/Al2O3 core-shell hollow nanotubes were prepared by combining electrospinning, atomic layer deposition, and a subsequent chemical reduction process. Electrospun poly(vinyl alcohol) (PVOH) nanofibers were obtained by electrospinning. Then, these fibers were coated with atomic layer deposition to obtain PVOH/Al2O3/NiO/Al2O3 core-shell nanowires. Since the NiO must be deposited at 200 °C, the PVOH nanofibers must first be coated with Al2O3 at 80 °C, which act as a protective layer of the fibers so that they can withstand higher temperatures. Once PVOH/Al2O3/NiO/Al2O3 core-shell nanowires are obtained, they are subjected to a chemical reduction process that generates Al2O3/Ni/Al2O3 core-shell hollow nanotubes. Their morphologies were studied by scanning and transmission electron microscopies, the thickness was determined by ellipsometry, and all magnetic measurements were performed in an alternating-gradient force magnetometer. Finally, assuming that the nanostructures exhibit a curling reversal process, the authors have analytically calculated the coercivity of the nanotubes. © 2018 Author(s).